2003
DOI: 10.1073/pnas.1033041100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the λ integrase surface that interacts with Xis reveals a residue that is also critical for Int dimer formation

Abstract: Lambda integrase (Int) is a heterobivalent DNA-binding protein that together with the accessory DNA-bending proteins IHF, Fis, and Xis, forms the higher-order protein-DNA complexes that execute integrative and excisive recombination at specific loci on the chromosomes of phage and its Escherichia coli host. The large carboxyl-terminal domain of Int is responsible for binding to core-type DNA sites and catalysis of DNA cleavage and ligation reactions. The small amino-terminal domain (residues 1-70), which speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The importance of integrase stability has also been demonstrated in the excision of a mycophage (which does not appear to require an RDF for excision) (54). The majority of RDFs that have been described are from prophages and were shown to control directionality of recombination by playing an architectural role by binding at the att sites, to each other, and/or to the integrase (20,21,24,(27)(28)(29)55). We determined that VefA and VefB bound the att sites of both islands, although VefB bound both sites at a higher affinity, causing a shift with four times less protein than VefA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of integrase stability has also been demonstrated in the excision of a mycophage (which does not appear to require an RDF for excision) (54). The majority of RDFs that have been described are from prophages and were shown to control directionality of recombination by playing an architectural role by binding at the att sites, to each other, and/or to the integrase (20,21,24,(27)(28)(29)55). We determined that VefA and VefB bound the att sites of both islands, although VefB bound both sites at a higher affinity, causing a shift with four times less protein than VefA.…”
Section: Discussionmentioning
confidence: 99%
“…In TR integrase-encoding prophages, it was demonstrated that the excision event also requires an additional protein, an excisionase or recombination directionality factor (RDF) (24)(25)(26)(27)(28). In fact, it is believed that all TR integrases require an RDF to perform excision (20,29).…”
mentioning
confidence: 99%
“…His Int ) that contains the DNA-binding and Xis cooperativity determinants (15)(16)(17). As shown in lane 2 of Fig.…”
Section: Used the N-terminal His-tagged Domain Of Int (mentioning
confidence: 99%
“…Xis bends DNA approximately 140 degrees (32) and can function as a multiprotein complex with the FIS (factor for inversion stimulation) protein when the concentration of Xis is limiting (6, 33). The Xis is the best characterized of the Xis proteins because its residues involved in DNA binding (8,27) and in cooperative interactions with Int (7,9,24,31,34) have been identified, its structure has been solved by nuclear magnetic resonance spectroscopy (28), and a DNA-Xis cocrystal structure has been solved (26,27). Bacteriophage L5 Xis and P2 Xis (11,22,23,37) and the HP1 Cox protein (13-15) have also been studied.…”
mentioning
confidence: 99%